Structured targets for advanced laser-driven sources. (6th November 2017) - Fedeli, L; Formenti, A; Cialfi, L; Sgattoni, A; Cantono, G; Passoni, M
Abstract: Structured targets offer great control over ultra-intense laser-plasma interaction, allowing the optimization of laser-target coupling for specific applications. By means of particle-in-cell simulations we investigated three applications in particular: high-order harmonic generation (HHG) with grating targets, enhanced target coupling with multilayer targets and the generation of intense laser-driven terahertz (THz) pulses with structured targets. The irradiation of a solid grating target at the resonance angle for surface plasmon excitation enhances the HHG with respect to flat targets. Multilayer targets consisting of solid foils coated with a very low-density near-critical layer lead to a strong laser absorption and hot electron production that can improve laser-driven ion acceleration. We also explored the generation of THz radiation showing how using either gratings or multilayer targets the emission can be strongly enhanced with respect to simple flat targets.